Efficacy and safety assessment of a TRAF6-targeted nanoimmunotherapy in atherosclerotic mice and non-human primates. (May 2018) - Lameijer, Marnix; Binderup, Tina; van Leent, Mandy; Senders, Max; Fay, Francois; Malkus, Joost; Sanchez-Gaytan, Brenda; Teunissen, Abraham; Karakatsanis, Nicolas; Robson, Philip; Zhou, Xianxiao; Ye, Yuxiang; et al.
Abstract Macrophage accumulation in atherosclerosis is directly linked to the destabilization and rupture of plaque, causing acute atherothrombotic events. Circulating monocytes enter the plaque and differentiate into macrophages, where they are activated by CD4+ T lymphocytes through CD40–CD40 ligand signalling. Here, we report the development and multiparametric evaluation of a nanoimmunotherapy that moderates CD40–CD40 ligand signalling in monocytes and macrophages by blocking the interaction between CD40 and tumour necrosis factor receptor-associated factor 6 (TRAF6). We evaluated the biodistribution characteristics of the nanoimmunotherapy in apolipoprotein E-deficient (Apoe –/– ) mice and in non-human primates by in vivo positron-emission tomography imaging. InApoe –/– mice, a 1-week nanoimmunotherapy treatment regimen achieved significant anti-inflammatory effects, which was due to the impaired migration capacity of monocytes, as established by a transcriptome analysis. The rapid reduction of plaque inflammation by the TRAF6-targeted nanoimmunotherapy and its favourable toxicity profiles in both mice and non-human primates highlights the translational potential of this strategy for the treatment of atherosclerosis. A nanoparticle-based immunotherapy targeted to a protein responsible for signalling between monocytes and macrophages reduces plaque inflammation in atherosclerotic mice and appears to be safe in non-human primates.